4Q148 (4QPhylactère U) Another Amulet from Qumran? - Feldman, Ariel 1974-; Feldman, Faina (2019)
This contribution is the first attempt at deciphering a miniature opistograph 4Q148 included in Józef T. Milik's DJD 6 edition of tefillin and mezuzot from Qumran Cave 4. It proposes that the partially folded recto of this tiny fragment contains a non- scriptural text. A handful of legible words may suggest a prayer. Its verso, inscribed by a different hand, appears to be a legal text, evoking monetary amounts, perhaps related to inheritance. Folded and fastened similarly to tefillin, 4Q148 might have been a legal document re-used to produce an amulet.
Keywords: 4Q148; Amulet; Apotropaic; Inheritance; phylactery; Prayer; Tefillin